2011
DOI: 10.1371/journal.pone.0023765
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and Actions of an Arylaspartate Inhibitor of Glutamate Transport at the Schaffer Collateral-CA1 Pyramidal Cell Synapse

Abstract: In this study we characterized the pharmacological selectivity and physiological actions of a new arylaspartate glutamate transporter blocker, L-threo-ß-benzylaspartate (L-TBA). At concentrations up to 100 µM, L-TBA did not act as an AMPA receptor (AMPAR) or NMDA receptor (NMDAR) agonist or antagonist when applied to outside-out patches from mouse hippocampal CA1 pyramidal neurons. L-TBA had no effect on the amplitude of field excitatory postsynaptic potentials (fEPSPs) recorded at the Schaffer collateral-CA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…We conclude that, consistent with the results in [32], non-local glial transporters are primarily responsible for limiting spill-over of synaptically released glutamate, and we establish mathematically that a model of co-localized transporters and receptors (as would be the case with neuronal transporters) cannot reproduce the paired pulse experimental results with L-TBA.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We conclude that, consistent with the results in [32], non-local glial transporters are primarily responsible for limiting spill-over of synaptically released glutamate, and we establish mathematically that a model of co-localized transporters and receptors (as would be the case with neuronal transporters) cannot reproduce the paired pulse experimental results with L-TBA.…”
Section: Discussionsupporting
confidence: 87%
“…The action of neurotransmitter transporters is key in many of these studies, since the inhibition of these transporters can lead to excess neurotransmitter in the extracellular space. More recent studies of this phenomenon include Scimemi et al [30] and Sun et al [32]. An overview of glutamate spill-over and transporter action is given in Diamond [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some immunocytochemical studies conducted before EAAC1 knock-out mice became available noted labeling of GABAergic terminals (He et al, 2000(He et al, , 2001 in the deep cerebellar nuclei (Rothstein et al, 1994). A study based on antisense knockdown concluded that EAAC1 is important for GABA synthesis in GABAergic terminals (Sepkuty et al, 2002), but the antisense probes used may have had unrecognized effects because EAAC1 knockdown using the same method (Rothstein et al, 1996) lead to a larger reduction in glutamate uptake activity than can be attributed to this transporter (see data in the studies by Danbolt et al, 1992;Haugeto et al, 1996;Jahr, 1997, 1998;Peghini et al, 1997;Tanaka et al, 1997;Furness et al, 2008;Sun et al, 2011).…”
Section: Is Eaac1 Present In Nerve Terminals?mentioning
confidence: 99%
“…In contrast, the role of EAAC1 (EAAT3) is still debated. Immunoisolation of transport activity (Haugeto et al, 1996), deletion of the GLT-1 (slc1a2) gene Jahr, 1997, 1998;Tanaka et al, 1997;Sun et al, 2011), and the mild phenotype of EAAC1-deficient mice (Peghini et al, 1997) suggest that EAAC1-mediated glutamate uptake is negligible compared with that of GLT-1. However, EAAC1-deficient mice suffer from dicarboxylic aminoaciduria (Peghini et al, 1997) and premature aging (Chen and Swanson, 2003;Aoyama et al, 2006;Berman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%